Explaining the Wealth Holdings of Different Cohorts: Productivity Growth and Social Security - Arie Kapteyn; Rob Alessie; Annamaria Lusardi (Tinbergen Institute, 1999)
It is well-known that individuals born in different periods of time (cohorts)exhibit different wealth accumulation paths. While previous studies have usedcohort dummies to proxy for this fact, research in this area suffers from aserious identification problem, i.e., how to disentangle age, time, and cohorteffects from a simple cross-section or a time series of cross-sections.In this paper we propose to go beyond the simple use of cohort dummies to capture the differences inwealth accumulation across individuals born in different time periods. We introduce two indicators of theeconomic conditions under which households accumulate wealth. The first one represents productivitydifferences across cohorts: the aggregate level of GNP per capita when the head of the household entered thelabor market. The second measure summarizes the changes in Social Security during the head ofhousehold?s working life. The use of these indicators also gets around the identification problem.We estimate the model using panel data from the Netherlands. This is a country whose historicalconditions are ideal to study the effects of productivity growth and Social Security. The Netherlandsexperienced a steady growth after World War II. At the same time, it also built up a very extensive welfaresystem. Our empirical findings show that productivity growth goes a long way in explaining differences inincome across cohorts. Productivity growth and Social Security can explain most, if not all, of thedifferences in wealth holdings of different cohorts. In comparison with the cohorts that lived without SocialSecurity for a portion of their working life, the cohorts that had Social Security throughout their working lifehave less than half the accumulation rate of older cohorts.
Keywords: D91; C23; 330; Wealth Accumulation; Productivity Growth; Social Security; Vermögensverteilung; Generationengerechtigkeit; Soziale Sicherheit; Wirtschaftswachstum; Niederlande